(untitled) (Malaysian Management Journal, 2017)
This study investigates the relationships and impact of social competencies on job performance and the mediating role of cultural adjustment of expatriates engaged in the ICT sector in Malaysia. Based on a quantitative survey with a sample of 301 expatriates, the findings of this study revealed that social competencies have a positive relationship with job performance. The findings also support the role of cultural adjustment in mediating the relationship between social competencies and job performance. The findings of this study support the results from some earlier studies and also bring out several new ideas such as the importance of social competencies. The findings of this study will significantly contribute to the advancement of knowledge in job performance and cultural adjustment and it is evident that expatriate social competencies facilitate expatriates’ job performance and cultural adjustment. The implications are in the areas of expatriate selection, training and support practices. It is recommended that organizations consider social competencies and cultural adjustment and implement suitable HR policies to select the right candidates, train and motivate them. The results of this study will add to the current body of knowledge as well as assist in creating foundational solutions to ensure success in expatriate global assignments in Malaysia.